Cooking quality: physical and biochemical properties of lentils (Lens culinaris). - Sheung-kei, Winnie S (Curtin University, 2000)
Lentils, one of the cool-season pulses, are consumed as a staple food in most developing countries. The demand for pulses in western societies is increasing because of its valuable nutritional quality and an increased awareness of health issues. Australia has a good reputation for producing clean low moisture legume products and could increase as market share of lentil production by identifying, developing and promoting good quality varieties.Lentils which are graded as good quality varieties must have a short and uniform cooking time, without 'hard to cook' seed, have the hull stay attached to the seed during cooking, and have a final acceptable taste, texture, flavour and appearance after cooking (Bhatty 1990). Cooking quality in this study is defined as the maximum force (N) that is required to compress the whole seed cooked product after cooking for a standard period of time. This study aims to develop an objective measurement to determine the cooking quality of lentils and thereby evaluates the relationships between lentil cooking quality and some of its physical and biochemical properties. Four cultivars used (Cassab, Digger, ILL 7180 and Matilda) were grown during 1999 at Mullewa and Pingaring, Western Australia. The relationship between the cooking quality of lentil and water absorption, seed size, seed coat thickness, phytic acid, mineral composition and initial moisture content was investigated.Texture measurement was carried out using the TA.XT2i meter as an alternative to the subjective method "Cooking time test". By comparing the cooking time determined by 'Cooking time test, 220 N was established and suggested as an optimal peak compression force to determine the adequate cooking time for lentils. Both methods showed that 35 minutes cooking time was adequate for red lentils (Cassab, Digger, and ILL 7180), and 45 minutes for green lentils (Matilda).Cooking significantly reduced the hardness of the seeds (R= - 0.752 to - 0.89) and promoted mineral leaching (P < 0.05). The interaction between environment and genotype had a significant effect on seed size, seed coat thickness, mineral composition (Phytic acid, Ne, K+, Mg2+, Ca2+ M+, Fe2+ and CU2+) and hardness (P< 0.05). Seed coat thickness did not correlated with this rate of water uptake and cooking quality. Growing environments had a greater influence on the cooking quality than genotypes. Lentils grown at Pingaring are generally had a higher in Phyti acid content, better mineral retention and were harder in texture than those grown at Mullewa.The results of this study implicated that the peak compression force (220 N) was identified as an indicator to determine the cooking time of lentil cultivars. Texture Profile Analysis (TPA) is a useful method to evaluate various texture characteristics (hardness, cohesiveness, chewiness, springiness, gumminess and adhesiveness) of lentil cultivars. Cooking quality of lentil is significantly affected by the effect of varieties and growing locations. However, not the various biochemical compositions (phytic acid and minerals) and the thickness of seed coat have no significant effect on the cooking quality of lentil.